Time allocation and assimilation of foreign workers: Evidence from Spain - Caparrós-Ruiz, Antonio (My University, 2015)
The assimilation of immigrant workers to the Spanish labour market is a topic widely addressed by the economic literature. However, a little explored issue is the time allocation of immigrants and its effects on their integration and convergence to Spanish workers. This paper aims to study the time use of immigrants among different activities, and the influence of personal and family characteristics on the participation and the amount of time spent in each activity. The results will be compared to those obtained for the native workers, in order to detect possible similarities and differences between both groups (immigrants versus natives). The data used come from the Time Use Survey for the periods 2002-2003 and 2009-2010 (INE, 2004, 2011), which allows analysing the evolution of the time use’s patterns of the immigrant and native workers at the beginning of the 21first century. Censored regression models are applied because the time spent in different activities is a left-truncated variable. The traditional approximation to the left-truncation is a Tobit model, but it assumes that the underlying process determining the participation and the time spent in each activity are similar, which is quite restrictive. To solve this restriction a double hurdle model is applied.
Keywords: España - Inmigración; Time use; Inmigrants